PROPHETIC HADITH IN SUNNI AND SHI’ITE VIEWS: THE ANALYSIS OF HADITH AND TAFSIR SCIENCES - Nurrohman, Muhamad Ridwan (Journal of Islamicate Studies, 2019)
This paper aims to conduct a review of the Sunni and Shi'i rationale in looking at hadith. The highlight was about the basic conception of Shi'i which included the words ma'shum of the Imams as part of the 'Prophet's' Hadith which could be believed to be true. Its appearance in the Shi’i reference hadith books also, when viewed from a Sunni perspective, the number is quite problematic. Compared with opinions that are directly based on the Prophet or Ali, these books are actually more dominated by the opinion of the sixth generation Imam (Ja'far as-Sadiq). So, this paper discusses how solid the foundation of the conception is when compared to the famous conception of jumhur in the Sunni tradition.